Philosophy, Travel, and Place Being in Transit (Springer International Publishing, 2018)
This book continues the exploration of themes either neglected or devalued by others working in the field of philosophy and culture. The authors in this volume consider the domain of travel from the broadest and most diverse of philosophical perspectives, covering everyday topics ranging from commuting and vacation travel to immigration and forced relocation. Our time in transit, our being in transit, and our time at rest, whether by choice or edict, has always been at issue, always been at play (and has always been in motion, if you will), for our species. The essays collected here explore the possibilities of the material impact of being able to move or stay put, as well as being forced to go or prevented from leaving.